2021
DOI: 10.1007/jhep10(2021)192
|View full text |Cite
|
Sign up to set email alerts
|

Beta functions for the duality-invariant sigma model

Abstract: The O(d, d) invariant worldsheet theory for bosonic string theory with d abelian isometries is employed to compute the beta functions and Weyl anomaly at one-loop. We show that vanishing of the Weyl anomaly coefficients implies the equations of motion of the Maharana-Schwarz action. We give a self-contained introduction into the required techniques, including beta functions, the Weyl anomaly for two-dimensional sigma models and the background field method. This sets the stage for a sequel to this paper on gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 41 publications
(80 reference statements)
2
15
0
Order By: Relevance
“…In [1] we computed the complete duality invariant one-loop beta function for bosonic string theory in a Kaluza-Klein formulation with n external and d internal coordinates (with target-space fields being independent of the internal coordinates), completing earlier results in [7,8]. We showed that vanishing of the Weyl anomaly implies the two-derivative equations determined by Maharana and Schwarz [9].…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…In [1] we computed the complete duality invariant one-loop beta function for bosonic string theory in a Kaluza-Klein formulation with n external and d internal coordinates (with target-space fields being independent of the internal coordinates), completing earlier results in [7,8]. We showed that vanishing of the Weyl anomaly implies the two-derivative equations determined by Maharana and Schwarz [9].…”
Section: Introductionsupporting
confidence: 63%
“…However, the anomalous transformation of the one-loop effective action can be canceled by using the Green-Schwarz mechanism, assigning a suitable transformation to the external B-field. This observation gives a worldsheet interpretation to the target-space analysis in [11,12] that showed that in general O(d, d) transformations need to be α -deformed, 1 although this deformation vanishes in the cosmological setting that we focus on here. Similarly, a theory of chiral bosons generally displays gravitational anomalies, but one expects that for an equal number of left-moving and right-moving bosons, as in Tseytlin's model, these anomalies cancel [28][29][30].…”
Section: Jhep02(2022)109mentioning
confidence: 71%
See 3 more Smart Citations